COSMOPOLITANISM AS SOCIOLOGICAL PERSPECTIVE ON AMERICAN LIFE IN THE ERA OF 1980-1990s THROUGH RAE LAWRENCE’S JACQUELINE SUSSAN’S SHADOW OF THE DOLLS - Ishaq Destri; Imam Basuki; Agung Tri (Fakultas Ilmu Budaya Universitas Jember, 2014)
This article discusses cosmopolitanism as sociological perspective on American life in the era of 1980- 1990s through Rae Lawrence’s Jacqueline Sussan’s Shadow of the Dolls. This article has two questions asked as the main problems which are also be the main goals in doing the research. The first question asks about the characters’ life styles. The second question is about American perspective on cosmopolitanism in certain era based on the novel. This research uses sociology perspective in understanding the form of cosmopolitanism from the characters’ life styles based on Swingewoods’ theory. This research is a qualitative research and a documentary method is used to collect the data, as well as the inductive method which is used to analyze the subject matters. After doing the research, we found that the characters in the novel are represented as cosmopolitan who have their own choices in life. Besides, we also found that life styles as society’s perspective lead society to choose cosmopolitan as their way of life. Keywords: Cosmopolitanism, Sociological Perspective, Lifestyle